2022
DOI: 10.1002/cpe.6883
|View full text |Cite
|
Sign up to set email alerts
|

A novel COVID‐19 sentiment analysis in Turkish based on the combination of convolutional neural network and bidirectional long‐short term memory on Twitter

Abstract: The whole world has been experiencing the COVID‐19 pandemic since December 2019. During the pandemic, a new life has been started by necessity where people have extensively used social media to express their feelings, and find information. Twitter was used as the source of what people have shared regarding the COVID‐19 pandemic. Sentiment analysis deals with the extraction of the sentiment of a given text. Most of the related works deal with sentiment analysis in English, while studies for Turkish sentiment an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…However, our study differentiates with using different algorithms and datasets with different topics. On the other hand, another study [ 28 ] has very high accuracy over 15k tweets and CNN and bidirectional LSTM, which used a lexicon to label big number of data. As for us, in our study, we did not use lexicons; however, we used manually labeled dataset and SentimentSet that is created in the scope of the study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our study differentiates with using different algorithms and datasets with different topics. On the other hand, another study [ 28 ] has very high accuracy over 15k tweets and CNN and bidirectional LSTM, which used a lexicon to label big number of data. As for us, in our study, we did not use lexicons; however, we used manually labeled dataset and SentimentSet that is created in the scope of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Aydogan and Kocaman [ 26 ] offered a new dataset since there are limited Turkish datasets to work on. Lately, some COVID-19 related studies [ 28 – 31 ] can be found in the literature.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A novel sentiment analysis model based on the combination of convolutional neural network and bidirectional long short-term memory was proposed in this study. 29 proposed deep neural network model using 15, 000 COVID-19 related Turkish tweets to classify into positive, negative, and neutral sentiment and obtained 97.9% accuracy. 30 identified trends, sentiment and emotions in nurses' COVID-19 related tweets from March to December 2020 using using AFINN, Bing, and NRC lexicon and 31 also performed analysis on Turkish nurses tweets to identify public perspective at the time of COVID-19 in Turkey.…”
Section: Related Workmentioning
confidence: 99%
“…Automatic text annotations can detect hate speech by applying machine learning methods with a semi-supervised learning approach [4,5]. Hate speech data are annotated using two categories (hate and not hate) [6][7][8][9][10], and using sentiment analysis methods, in which data are labeled using two or three categories, namely (positive and negative) [11,12], or (positive, negative, and neutral) [13][14][15][16]. We develop automatic annotations by utilizing a dataset with minimal labeled training data and incorporate self-learning for labels.…”
Section: Introductionmentioning
confidence: 99%